Women's Lived Experiences of Sexual and Reproductive Health Challenges in Temporary Marriage: A Phenomenological Study - Fatemeh Ghasemi; Ghodratolah Khosroshahi; Amir Ghamarani; Mahnaz Noroozi (Strategic Research on Social Problems)
IntroductionTemporary marriage can address the sexual needs and health of couples; however, it may also present significant sexual and reproductive health challenges for women. Factors, such as low self-esteem, traditional gender beliefs, and a lack of sexual awareness, often contribute to women's silence and passivity regarding unsafe sex, leading to various harms in temporary marriages. Identifying these challenges related to women's sexual and reproductive health is crucial for developing effective solutions. Previous research has not independently explored this issue using the phenomenological method in women with experience in temporary marriage. Therefore, this study aimed to investigate women's lived experiences of sexual and reproductive health challenges within the context of temporary marriage through a phenomenological approach.  Materials & MethodsThis research employed a qualitative methodology with an interpretative-phenomenological approach. The target group consisted of women residing in Isfahan, who had experienced at least one temporary marriage. Purposeful sampling was conducted with maximum variation, utilizing the snowball method to identify participants. To achieve data saturation, semi-structured in-depth interviews were conducted with a sample of 12 women. Given the study's focus on describing the lived experiences of women facing sexual and reproductive health challenges in temporary marriages, the phenomenological approach, specifically the Diekelman method, was employed to capture and illustrate their experiences. To ensure the rigor and trustworthiness of the data, the criteria of credibility, confirmability, dependability, and transferability were applied. Discussion of Results & ConclusionDuring data analysis, 114 open codes were identified from a total of 273 codes, resulting in 12 categories and 3 main themes. The first theme, "Unintended Pregnancy and the Heavy Burden of Abortion Decisions", encompassed 4 categories:Imposition of Abortion and Lack of Male Responsibility and Support for WomenEnduring Psychological and Physical Suffering Post-AbortionPhysiological Stress Induced by Unintended AbortionsEnvironmental and Social Constraints on Supporting Women's Reproductive HealthThe second theme, "Negligence in Maintaining Sexual Health", included 4 categories:Ongoing Unawareness and Escalating Sexual Health IssuesWomen's Sexual Awareness and Attitudes Limited by Societal and Cultural PressuresSexual Attitudes Shaped by Social InteractionsInterconnectedness of the Body and Sexual HealthThe third theme, "Engaging in High-Risk Sexual Behaviors", consisted of 4 categories:Evolution of High-Risk Sexual Behaviors over TimeInstrumentalization of the Body in High-Risk Sexual RelationshipsEmergence of Unintended High-Risk Sexual Relationships in Uncertain EnvironmentsWomen’s Passivity in High-Risk Sexual InteractionsOverall, the findings suggested that various factors contributed to the challenges faced by women in temporary marriages. These included societal stigma surrounding temporary marriage, women's sexual passivity in relationships lacking male commitment rooted in patriarchal culture, difficulties in negotiating with men, traditional gender roles, insufficient sexual health education, and prevalence of harmful sexual attitudes. Consequently, these factors had led to unwanted pregnancies and coerced abortions, as well as increased engagement in risky sexual behaviors. Women in temporary marriages often experienced both physical and psychological harm from abortions and their involvement in high-risk sexual activities coupled with inadequate access to sexual healthcare heightened their vulnerability to HIV/AIDS, sexually transmitted infections, and unintended pregnancies.